Bendable Solar Cells from Stable, Flexible, and Transparent Conducting Electrodes Fabricated Using a Nitrogen‐Doped Ultrathin Copper Film. (13th April 2016) - Zhao, Guoqing; Kim, Soo Min; Lee, Sang‐Geul; Bae, Tae‐Sung; Mun, ChaeWon; Lee, Sunghun; Yu, Huashun; Lee, Gun‐Hwan; Lee, Hae‐Seok; Song, Myungkwan; Yun, Jungheum
Abstract : Copper has attracted significant interests as an abundant and low‐cost alternative material for flexible transparent conducting electrodes (FTCEs). However, Cu‐based FTCEs still present unsolved technical issues, such as their inferior light transmittance and oxidation durability compared to conventional indium tin oxide (ITO) and silver metal electrodes. This study reports a novel technique for fabricating highly efficient FTCEs composed of a copper ultrathin film sandwiched between zinc oxides, with enhanced transparency and antioxidation performances. A completely continuous and smooth copper ultrathin film is fabricated by a simple room‐temperature reactive sputtering process involving controlled nitrogen doping (<1%) due to a dramatic improvement in the wettability of copper on zinc oxide surfaces. The electrode based on the nitrogen‐doped copper film exhibits an optimized average transmittance of 84% over a spectral range of 380 −1000 nm and a sheet resistance lower than 20 Ω sq −1, with no electrical degradation after exposure to strong oxidation conditions for 760 h. Remarkably, a flexible organic solar cell based on the present Cu‐based FTCE achieves a power conversion efficiency of 7.1%, clearly exceeding that (6.6%) of solar cells utilizing the conventional ITO film, and this excellent performance is maintained even in almost completely bent configurations. Abstract : A highly stable, flexible, conductive, and transparent electrode based on a completely continuous, smooth nitrogen‐doped ultrathin Cu film is developed by an innovative room‐temperature reactive sputtering process. The electrode is employed to fabricate highly efficient bendable organic solar cells built on polymer substrates.